Comparative Transcriptomic and Expression Profiles Between the Foot Muscle and Mantle Tissues in the Giant Triton Snail Charonia tritonis - Zhang, Gege; Xu, Meng; Zhang, Chenglong; Jia, Huixia; Zhang, Hua; He, Maoxian; Liu, Wenguang (Frontiers in Physiology, 2021)
The giant triton snail (Charonia tritonis), an endangered gastropod species of ecological and economic importance, is widely distributed in coral reef ecosystems of the Indo-West Pacific region and the tropical waters of the South China Sea. Limited research on molecular mechanisms can be conducted because the complete genomic information on this species is unavailable. Hence, we performed transcriptome sequencing of the C. tritonis foot muscle and mantle using the Illumina HiSeq sequencing platform. In 109,722 unigenes, we detected 7,994 (3,196 up-regulated and 4,798 down-regulated) differentially expressed genes (DEGs) from the C. tritonis foot muscle and mantle transcriptomes. These DEGs will provide valuable resources to improve the understanding of molecular mechanisms involved in biomineralization of C. tritonis. In the Gene Ontology (GO) database, DEGs were clustered into three main categories (biological processes, molecular functions, and cellular components) and were involved in 50 functional subcategories. The top 20 GO terms in the molecular function category included sulfotransferase activity, transferring sulfur-containing groups, and calcium ion binding, which are terms considered to be related to biomineralization. In KEGG classifications, transcriptomic DEGs were mainly enriched in glycosaminoglycan biosynthesis-chondroitin sulfate/dermatan sulfate, and sulfur metabolism pathway, which may be related to biomineralization. The results of qPCR showed that three of the eight genes examined were significantly up-regulated in the mantle. The phylogenetic tree of BMP1 suggested a significant divergence between homologous genes in C. tritonis. Our results improve the understanding of biomineralization in C. tritonis and provide fundamental transcriptome information to study other molecular mechanisms such as reproduction.